2022-RA-671-ESGO Identification of risk factors of recurrence among patients with vulvar Paget`s disease treated with conservative surgery: a retrospective cohort. (20th October 2022) - Pergialiotis, Vasilios; Christodoulou, Theano; Ferousis, Loukas; Thomakos, Nikolaos; Rodolakis, Alexandros; Haidopoulos, Dimitrios
Abstract : Introduction/Background: Vulvar Paget`s disease is a benign disease with high recurrence rates. Standard treatment involves conservative surgery with wide local excision of the lesion. The purpose of the present study is to identify factors that increase the risk of relapse. Methodology: We conducted a retrospective study and included patients treated with conservative surgery for non-invasive vulvar Paget`s disease. Cox regression analysis was carried out to assess the independent effect of age, presence of positive margins, tumor size >4 cm, bilateral lesions and compositive morbidity and pathology on recurrence free survival. Post hoc power analysis was performed with the G-power tool using an alpha error of 0.05. Results: Overall, 39 patients were included with a median age of 70 years (46–85). Of those 19 patients relapsed within a median duration of 30.5 months (5–132 months). Twelve patients (63%) experienced at least a second relapse. The presence of composite co-morbidity significantly affected the interval to recurrence (30.09 months vs 71.80 months, p=.032). Univariate Cox-regression analysis revealed that the presence of composite pathology features was indicative of a higher risk of recurrence (HR -3.71, p=.024). The sample size did not allow for adequate power for this latter finding. Microscopically involved tumor margins and tumor size >4 cm did not predict patients at risk of experiencing relapsing disease. Conclusion: Patients with non-invasive vulvar Paget`s disease experience high relapse rates. The presence of concurrent benign vulvar pathology may increase these rates, although larger sample sizes are needed to ascertain our findings.